2016
DOI: 10.1016/j.revpalbo.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Fables and foibles: A critical analysis of the Palaeoflora database and the Coexistence Approach for palaeoclimate reconstruction

Abstract: The 'Coexistence Approach' is a mutual climate range (MCR) technique combined with the nearest-living relative (NLR) concept. It has been widely used for palaeoclimate reconstructions based on Eurasian plant fossil assemblages; most of them palynofloras (studied using light microscopy). The results have been surprisingly uniform, typically converging to subtropical, per-humid or monsoonal conditions. Studies based on the Coexistence Approach have had a marked impact in literature, generating over 10,000 citati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 74 publications
(265 reference statements)
0
16
0
Order By: Relevance
“…This assumption inevitably introduces uncertainty that increases with the age of the geological record. Grimm et al (2016) demonstrated how the incorrect use of outliers and fossil taxa with ambiguous affinity, as well as insufficient documentation of modern distribution of the NLR, can result in erroneous climate estimates from the CA. By its nature, the NLR approach cannot accurately predict environmental conditions beyond the present-day range.…”
Section: Weaknesses Of the Coexistence Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This assumption inevitably introduces uncertainty that increases with the age of the geological record. Grimm et al (2016) demonstrated how the incorrect use of outliers and fossil taxa with ambiguous affinity, as well as insufficient documentation of modern distribution of the NLR, can result in erroneous climate estimates from the CA. By its nature, the NLR approach cannot accurately predict environmental conditions beyond the present-day range.…”
Section: Weaknesses Of the Coexistence Approachmentioning
confidence: 99%
“…For instance, maximum LAT estimates plateau at ~25 for CA (Utescher et al, 2014). presented with confidence ranges including the uncertainty associated with the estimate of climate tolerances (Grimm et al, 2016). For comparisons using larger datasets, each climate estimate should be rated using a qualitative ranking system (i.e.…”
Section: Weaknesses Of the Coexistence Approachmentioning
confidence: 99%
“…Boron-based CO 2 reconstructions spanning the last ∼800 000 years show excellent agreement with ice core CO 2 estimates (Hönisch et al, 2009). The results of boron isotope studies have also been found to be highly reproducible between different laboratories Gutjahr et al, 2017), allowing the integration of multiple datasets and providing high confidence in the fundamental measurement of boron isotopes in biogenic carbonates. In common with other marine CO 2 proxies (e.g., alkenones below), age constraints are also typically strong for δ 11 B c and it is easy to correlate the resultant CO 2 estimates with marine-based climate proxies, some of which can be measured on the same material (e.g., δ 18 O, 47 and Mg/Ca in planktic foraminifera).…”
Section: Strengths Of Boron-based Co 2 Reconstructionsmentioning
confidence: 63%
“…This method permits to analyze also carpological data and to compare the two types of fossil associations. This method provides a robust palaeoclimatic proxy although its reliability has been questioned by some authors (Grimm and Denk 2012;Grimm et al 2016). A lot of studies were undertaken for testing different climate reconstruction methods (CAMethod, LMA, CLAMP, ELPA, etc.…”
Section: Methods For Vegetation and Climate Reconstructionsmentioning
confidence: 99%